Electroluminescent substrate and preparation method thereof, luminescent device and luminescent method thereof

Through the electrode layer combined with the silk fibroin and conductive substance and the elastic luminescent layer doped with metal particles, the luminescent stability and self-healing ability of the electroluminescent matrix during stretching are improved, and the poor luminescent stability and in the prior art are solved. The problem of insufficient recovery ability is suitable for complex applications.

CN119225083APending Publication Date: 2024-12-31SHANGHAI TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310776480.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing electroluminescent matrix has poor luminescence stability when stretched and is difficult to recover after being subjected to mechanical and environmental stimulation, which cannot meet the needs of complex applications.

Method used

Using an electrode layer combined with conductive substances (such as lithium and calcium salts) and an elastic luminescent layer of electroluminescent particles doped with metal elements, to increase intensity and elasticity through the β-sheet conformation of the silk fibroin, and use mediators The electroluminescent matrix is ​​formed by increasing the interface bonding intensity.

Benefits of technology

Maintain good and stable luminous intensity in the tensile state, has good mechanical strength and self-healing ability, and can work normally in cyclic stretching and extreme environments. It is suitable for complex human-computer interaction and display applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119225083A_ABST
    Figure CN119225083A_ABST
Patent Text Reader

Abstract

The invention discloses an electroluminescent substrate and a preparation method thereof, and a luminescent device and a luminescent method thereof. The electroluminescent substrate structurally comprises a first insulating layer, a first electrode layer, an elastic luminescent layer, a second electrode layer and a second insulating layer; each of the first electrode layer and the second electrode layer comprises a conductive substance and silk fibroin; wherein the elastic light-emitting layer comprises electroluminescent particles and an elastic polymer. The electroluminescent substrate provided by the invention can still maintain good luminescence stability during stretching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to an electroluminescent substrate and a preparation method thereof, a light-emitting device and a light-emitting method thereof. Background Art

[0002] In recent years, as the demand for smart materials continues to increase, luminescent display technology has attracted much attention and has been applied to health monitoring, safety warning, soft robotics and other fields. At the same time, it has achieved rapid development in the field of human-computer interaction to achieve "intelligent" communication with the brain. However, in the existing display devices in the field of human-computer interaction, the mechanics and functions still need to be further improved.

[0003] In terms of mechanics, display devices should have a touch and mechanical properties similar to human skin, that is, a soft physical form and excellent elasticity, and be able to fit with surfaces of different topological structures. In daily use, display devices should be able to withstand single or long-term cycles of mechanical and environmental stimuli, such as stretching, twisting and bending. After these complex mechanical stimuli are removed, the light-emitting device needs to quickly return to its original shape to maintain the accuracy of the display device. In some extreme applications, such as visual injury warnings and outdoor soft robots, these light-emitting devices even need to have self-healing capabilities after extreme damage such as corrosion, puncture and cutting. However, currently disclosed display devices are far from meeting these requirements. For example, stretchable, bendable and foldable display devices are usually prepared by assembling light-emitting diodes on elastic substrates to form serpentine or buckle structures. However, light-emitting diodes themselves are not stretchable, and their ultimate strain is less than 120%, which is much lower than the ultimate strain of elastomers. In addition, electroluminescent devices prepared by combining phosphor particles with elastomers have also been proven to be one of the practical methods for preparing highly stretchable display devices. However, in most reported design strategies, these electrode layers are usually composed of a composite of elastic polymers and conductive nanomaterials (such as silver nanowires, carbon nanotubes, and graphene). However, once the tensile strain exceeds a certain value, the connectivity of these nanomaterials will fall below the percolation threshold, resulting in a sharp drop in conductivity and affecting the luminescence performance of the device. In addition, this nanostructure cannot restore its original connectivity after being damaged. Therefore, these devices often experience functional instability or even failure during cyclic stretching.

[0004] From a functional point of view, light-emitting devices need to have the ability to eliminate the constraints of passive display and be able to combine with artificial intelligence and Internet of Things technologies to realize intelligent interaction between the display platform and the environment, human body, and machine. The interactive light-emitting display devices that have been reported so far mainly focus on tactile perception response, including capacitive response, piezoelectric-ionic effect, triboelectric effect, etc. However, tactile perception requires direct contact between the object and the display device, so the types of objects and environments that can be perceived are relatively limited. In addition, these devices are not easy to communicate and interact with the environment, human body, and machine. In order to overcome these problems, optical and acoustic signals can be used to realize the interaction between the display device and the environment. For example, the display device should have human-like audio-visual capabilities to analyze and process audio-visual information, so as to realize human-computer interactive display, question-and-answer display, thinking display, and even real-time dialogue display for semantic communication.

[0005] Therefore, how to provide an electroluminescent matrix that can maintain good luminescence stability when stretched is a technical problem that urgently needs to be solved in the art. Summary of the invention

[0006] In order to overcome the defect that the light-emitting device of the display device in the prior art cannot maintain good light-emitting stability when stretched, the present invention provides an electroluminescent matrix and a preparation method thereof, a light-emitting device and a light-emitting method thereof. The electroluminescent matrix provided by the present invention can still maintain good light-emitting stability when stretched.

[0007] The present invention provides an electroluminescent substrate, the structure of which includes a first insulating layer, a first electrode layer, an elastic luminescent layer, a second electrode layer and a second insulating layer;

[0008] Wherein, the first electrode layer and the second electrode layer both include conductive material and silk fibroin;

[0009] Wherein, the elastic light-emitting layer comprises electroluminescent particles and elastic polymer.

[0010] In the present invention, the silk fibroin (SF) at least includes silk fibroin in a β-folded conformation, and the presence of the β-folded conformation can increase the strength between the electrode layer and the elastic light-emitting layer, and improve the overall elasticity of the electroluminescent matrix. In the present invention, the silk fibroin is a natural high-molecular fiber protein extracted from silk, and its content accounts for about 70%-80% of silk.

[0011] In the present invention, the conductive material may be conventional in the art, preferably a metal salt; the metal salt is more preferably a lithium salt and / or a calcium salt.

[0012] Wherein, the lithium salt may be lithium chloride and / or lithium bromide.

[0013] Wherein, the calcium salt may be calcium chloride.

[0014] Wherein, the silk fibroin and the Li in the lithium salt + The mass ratio can be (12-18):1, such as 12:1, 17:1 or 18:1.

[0015] More preferably, the silk fibroin and the Ca in the calcium salt 2+ The mass ratio of may be (5-8): 1, for example 6: 1. In the present invention, the electroluminescent particles may be conventional in the art, preferably comprising ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles.

[0016] In the present invention, the elastic luminescent layer may further include dielectric nanoparticles, and the dielectric nanoparticles preferably include strontium titanate and / or barium titanate.

[0017] In the present invention, the elastic polymer may be conventional in the art, preferably including one or more of polydimethylsiloxane, polyurethane and silicone rubber, and the polyurethane is more preferably water-based polyurethane.

[0018] In the present invention, the first insulating layer and the second insulating layer are both formed of acrylic glue, such as transparent acrylic foam glue, specifically high-viscosity transparent acrylic foam glue, which is referred to as VHB glue in this specification.

[0019] In the present invention, the first insulating layer and the second insulating layer are connected at their edges and encapsulate the first electrode layer, the elastic light-emitting layer and the second electrode layer.

[0020] In some embodiments, the first electrode layer and the second electrode layer each include a plurality of electrode layer units cut into different shapes and / or the same shape, and the electrode layer units are arranged continuously or discontinuously; and the electrode layer units of the same shape in the first electrode layer and the second electrode layer are arranged one by one.

[0021] In the present invention, the first electrode layer and the second electrode layer are further provided with an electrical connection portion electrically connected to an external power source, and the electrical connection portion is preferably a conductive metal wire;

[0022] In the present invention, the thickness of the elastic light-emitting layer may be 0.05 mm-0.5 mm, for example, 0.1 mm.

[0023] In the present invention, the thickness of the first electrode layer and the second electrode layer can be independently selected from 0.05 mm to 0.5 mm, such as 0.15 mm.

[0024] In the present invention, the thickness of the first electrode layer and the second electrode layer can be the same or different. By designing the thickness parameter, the electroluminescent substrate can be used as a luminous skin attached to a wearable product.

[0025] The present invention also provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0026] S1. preparing the mixed solution into an electrode layer; the mixed solution comprising silk fibroin, a conductive substance and a solvent;

[0027] The composite slurry is prepared into an elastic luminescent layer; the composite slurry comprises electroluminescent particles and an elastic polymer;

[0028] The preparation order of the electrode layer and the elastic light-emitting layer is not specific;

[0029] S2. The electrode layers are respectively arranged at the opposite ends of the elastic light-emitting layer, which are respectively recorded as the first electrode layer and the second electrode layer; the first electrode layer and the second electrode layer are encapsulated by the first insulating layer and the second insulating layer to obtain the electroluminescent matrix.

[0030] In the present invention, the conductive material may be conventional in the art, preferably a metal salt; the metal salt is more preferably a lithium salt and / or a calcium salt.

[0031] Wherein, the lithium salt may be lithium chloride and / or lithium bromide.

[0032] Wherein, the calcium salt may be calcium chloride.

[0033] Wherein, the silk fibroin and the Li in the lithium salt + The mass ratio can be (12-18):1, such as 12:1, 17:1 or 18:1.

[0034] More preferably, the silk fibroin and the Ca in the calcium salt 2+ The mass ratio can be (5-8):1, for example 6:1.

[0035] In the present invention, the solvent may be conventional in the art, preferably one or more of water, ethanol and formic acid.

[0036] In the present invention, the mass ratio of the silk fibroin to the solvent may be (0.1-20):100, for example, 10:100.

[0037] In the present invention, the mass ratio of the conductive material to the solvent may be (0.1-10):100, preferably (1-6):100, such as 1:27, 1:23, 1:18 or 1:48.

[0038] In the present invention, the electroluminescent particles may be conventional in the art, preferably include ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are more preferably ZnS:Cu particles and / or ZnS:Al particles.

[0039] In the present invention, the composite slurry may further include dielectric nanoparticles, and the dielectric nanoparticles preferably include strontium titanate and / or barium titanate.

[0040] The mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-50):100, more preferably (10-40):100, for example 1:5.

[0041] The mass ratio of the electroluminescent particles, the dielectric nanoparticles and the elastic polymer is preferably (2-4):1:5, such as 2:1:5 or 4:1:5.

[0042] In the present invention, the elastic polymer may be conventional in the art, preferably including one or more of polydimethylsiloxane, polyurethane and silicone rubber, and the polyurethane is more preferably water-based polyurethane.

[0043] In the present invention, the mass ratio of the electroluminescent particles to the elastic polymer may be (1-20):10, preferably (2-15):10, such as 4:5 or 2:5.

[0044] In the present invention, the insulator, the first insulating layer and the second insulating layer may be formed of materials commonly used in the art, preferably formed of acrylic adhesive, such as transparent acrylic foam.

[0045] In step S1, the preparation method of the mixed solution can be a conventional method in the art, preferably, the conductive material is first dispersed in the solvent, and then the silk fibroin is dispersed therein.

[0046] The dispersion is preferably completed under stirring conditions, and the stirring rate is more preferably 100 r / min-1000 r / min, such as 150 r / min.

[0047] The dispersion time is preferably 5 min to 60 min, for example 40 min.

[0048] In some embodiments, in step S1, in the mixed solution, the conductive substance is lithium bromide, the solvent is water, and the concentration of the lithium bromide is 4-8 mol / L.

[0049] In some embodiments, in step S1, in the mixed solution, the conductive substance is calcium chloride, the solvent is ethanol and water, and the molar ratio of calcium chloride, ethanol and water is 1:2:(6-10).

[0050] In some embodiments, in step S1, in the mixed solution, the conductive substance is lithium chloride, the solvent is formic acid, and the molar ratio of lithium chloride to formic acid is 1:(20-50).

[0051] In some embodiments, in step S1, in the mixed solution, the conductive substance is calcium chloride, the solvent is formic acid, and the molar ratio of calcium chloride to formic acid is 1:(40-100).

[0052] In step S1, the time for preparing the electrode layer may be 48h-240h, for example 96h.

[0053] In step S1, the temperature for preparing the electrode layer may be 25-60°C, for example 25°C.

[0054] In step S1, the relative humidity of the environment for preparing the electrode layer may be 60%-90%, preferably 65%-85%, for example 65%, 70%, 75% or 80%.

[0055] In step S1, the preparation of the electrode layer is preferably performed in a closed environment.

[0056] In step S1, the electrode layer can be prepared by a conventional method in the art, preferably by placing the mixed solution on a substrate and drying it to obtain the electrode layer.

[0057] In step S1, the preparation method of the composite slurry can be a conventional method in the art, preferably dispersing the electroluminescent particles and the dielectric nanoparticles in an elastic polymer to form the composite slurry; the dispersion time is more preferably 60s; the dispersion temperature is more preferably 25°C.

[0058] In step S1, the elastic light-emitting layer is prepared by coating the composite slurry on a substrate to form the elastic light-emitting layer.

[0059] Wherein, the material of the substrate is preferably PS and / or PET.

[0060] The coating method is preferably spin coating, spray coating or scraping coating; more preferably, the spin coating speed is 200 r / min-5000 r / min, such as 1000 r / min.

[0061] Preferably, curing is further performed after coating; more preferably, the curing temperature is 20°C-60°C, such as 60°C; more preferably, the curing time is 5min-120min, such as 60min.

[0062] In step S1, the elastic light-emitting layer is preferably subjected to a hydrophilic treatment; the method of the hydrophilic treatment is preferably at least one of an ultraviolet method, an ozone method and a plasma cleaning method; the time of the hydrophilic treatment is preferably 10s-60s. The elastic light-emitting layer is subjected to a hydrophilic treatment by ultraviolet / ozone treatment and / or plasma cleaning, which can not only improve the interface bonding strength when the elastic light-emitting layer is combined with the electrode layer composed of silk fibroin, but also keep the luminescent performance of the electroluminescent matrix stable during the stretching process.

[0063] In step S1, the first electrode layer and the second electrode layer each include a plurality of electrode layer units cut into different shapes and / or the same shapes, and the electrode layer units are arranged continuously or discontinuously; and the electrode layer units of the same shape in the first electrode layer and the second electrode layer are arranged one by one.

[0064] In step S2, an electrical connection portion electrically connected to an external power source is further provided in the electrode layer. During the packaging process, the electrical connection portion is exposed to the outside; the electrical connection portion is preferably a conductive metal wire.

[0065] The present invention also provides an electroluminescent matrix prepared by the above-mentioned preparation method.

[0066] The present invention also provides an application of the electroluminescent matrix as described above in the field of light-emitting display devices.

[0067] The present invention also provides a light-emitting device, which comprises the electroluminescent substrate, sensor and processor as described above.

[0068] In the present invention, the sensor may be a light sensor and / or a sound sensor.

[0069] In the present invention, the electroluminescent substrate is electrically connected to the processor and is used to emit light according to a preset pattern.

[0070] The present invention also provides a method for controlling the light emission of the light emitting device as described above, which comprises the following steps:

[0071] Get external signals;

[0072] Inputting the signal into a preset model to obtain a voltage signal;

[0073] According to the voltage signal, the output voltage between the first electrode layer and the second electrode layer is controlled, so that the elastic light-emitting layer is powered on and emits light, so as to form a pattern signal matching the external signal.

[0074] In some embodiments, the light-emitting device is applied to hearing-impaired equipment, for example, the machine learning recognition result, i.e., the type and frequency of the sound, is displayed in real time on a tkinter interface. At the same time, a single-chip microcomputer connected to a PC converts the recognition result into a "utf-8" format, drives the electroluminescent matrix skin to display the recognition result in real time, and can provide real-time alarms for hearing-impaired patients.

[0075] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0076] The reagents and raw materials used in the present invention are commercially available.

[0077] The positive and progressive effects of the present invention are:

[0078] (1) The electroluminescent matrix obtained by combining the elastic luminescent layer with the electrode layer composed of silk fibroin can maintain a good and stable luminescent intensity in the stretched state. Moreover, in the case of cyclic stretching, it can maintain a good and stable luminescent state to stably form the required luminescent pattern, so that the electroluminescent silk protein ion skin can withstand cyclic stress and strain in luminescent display applications. The electroluminescent matrix provided by the present invention can maintain a luminescent intensity equivalent to that in the initial state when the stretched length is 400%; it can still maintain luminescence when the stretched length is 700%. When the stretched length is 200%, the luminescent intensity remains at a level equivalent to that in the initial state after 100 cycles.

[0079] (2) The electroluminescent matrix provided by the present invention also has good mechanical strength, elastic properties and self-healing ability.

[0080] The elongation at break is above 400%, and some preferred embodiments can reach 600% or 800% or more, the fracture strength is not less than 0.2MPa, the Young's modulus is not less than 1.2MPa, and the toughness is not less than 1.6MJ m -3 The initial luminous intensity is 32 cd m -2 -86cd m -2 .

[0081] After splicing self-healing, a stable two-color luminescence state can still be achieved when its length is stretched to 300%.

[0082] (3) By combining the electroluminescent substrate of the present invention with the corresponding sensor and processor, the preset signal can be collected and the corresponding recognition model can be established, and the real-time signal can be converted into a preset electrical signal that matches the preset pattern, thereby controlling the electroluminescent substrate to emit light according to the preset pattern and light-emitting frequency, thereby having a good application scenario. By integrating the Internet of Things and machine learning technology, the above-mentioned electroluminescent substrate can realize accurate sound category recognition and audio-visual voice interaction, and can be widely used in the fields of human-computer interaction interface, soft robots, medical devices for hearing-impaired patients, etc.

[0083] (4) The silk fibroin used in the present invention is mainly derived from silk protein, which has the advantages of a wide range of raw material sources, being pure natural, sustainable, and biodegradable. In addition, the electroluminescent matrix prepared by combining with other components can also work normally under extreme environments and complex mechanical loads.

[0084] (5) The preparation process of the electroluminescent matrix of the present invention is simple to operate, requires few equipments, is energy-saving and highly efficient, and the prepared electroluminescent matrix has the ability to be scalable for production and has good application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Reference numerals: first insulating layer 10 , first electrode layer 20 , elastic light-emitting layer 30 , second electrode layer 40 , second insulating layer 50 .

[0086] Figure 1 Schematic diagram of the structure of the electroluminescent substrate in Example 1.

[0087] Figure 2 It is a schematic diagram of the structure of the electroluminescent substrate in the present invention.

[0088] Figure 3 Schematic diagram of the preparation process of the electroluminescent matrix in Example 1.

[0089] Figure 4 Different patterns emitted by the electroluminescent substrate provided in Example 1 when attached to a finger.

[0090] Figure 5 This is a schematic diagram of the state in which the electroluminescent substrate provided in Example 5 still works normally under low temperature and high temperature environments.

[0091] Figure 6 This is a graph showing the luminescence stability of the electroluminescent substrate provided in Example 2 during the process of being stretched to 700%.

[0092] Figure 7 The elastic properties of the electroluminescent substrate provided for Examples 2 and 3 are shown in the figure.

[0093] Figure 8Schematic diagram of the luminescence stability of the electroluminescent substrate provided in Example 2 during 100 cycles of stretching to 200%.

[0094] Fig. 9 Schematic diagram of the luminescence stability of the self-healed two-color electroluminescent matrix provided in Example 4 during the process of stretching to 300%.

[0095] Fig.10 Schematic diagram of the state of the human-computer interaction interface and the electroluminescent substrate when displaying a luminous pattern.

[0096] Fig.11 This is a schematic diagram of the structure of the smart light-emitting device attached to the back of the hand.

[0097] Fig.12 Schematic diagram of the relationship between the conductive properties of the electroluminescent matrix and the mass ratio of SF to LiCl.

[0098] Fig.13 Schematic diagram of the relationship between the luminescence intensity of the electroluminescent matrix, the mass ratio of SF to LiCl, and the applied voltage. DETAILED DESCRIPTION

[0099] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0100] In the following embodiments of the present invention, the thickness of the first electrode layer and the second electrode layer is 0.15 mm; the thickness of the elastic light-emitting layer is 0.1 mm.

[0101] The doping concentration of Cu in the electroluminescent particles ZnS:Cu used in Examples 1-2 and 5-13 of the present invention is the same.

[0102] Example 1

[0103] This embodiment provides a method for preparing an electroluminescent substrate, the structural schematic diagram of which is shown in FIG. Figure 1 and Figure 2 It is shown that it includes the following steps:

[0104] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 27:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0105] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 65% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0106] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane and stirring at 25°C and 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 4:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0107] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to solidify it, and performing plasma treatment to obtain an elastic light-emitting layer 30;

[0108] (5) transferring the electrode layer prepared in step (2) to the silicone oil paper as a soft substrate; after transferring the elastic light-emitting layer 30 to the first electrode layer 20, covering the second electrode layer 40 on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; using VHB glue as the first insulating layer 10 and the second insulating layer 50 respectively on opposite sides of the body to be packaged, and packaging it into an electroluminescent matrix, Figure 3 A schematic diagram of its preparation process is provided.

[0109] Example 2

[0110] This embodiment provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0111] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 23:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0112] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 75% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0113] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, uniformly dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane at 25°C and stirring at a speed of 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 2:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0114] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0115] (5) transferring the electrode layer prepared in step (2) to the silicone oil paper as a soft substrate; after transferring the elastic light-emitting layer 30 to the first electrode layer 20, covering the second electrode layer 40 on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; using VHB glue as the first insulating layer 10 and the second insulating layer 50 respectively on opposite sides of the body to be packaged, and packaging them into an electroluminescent matrix A;

[0116] Example 3

[0117] The ZnS:Cu in step (3) of Example 2 was replaced by ZnS:Al, and the other steps of Example 2 were repeated to obtain an electroluminescent matrix B.

[0118] Example 4

[0119] The electroluminescent matrix A prepared in Example 2 and the electroluminescent matrix B prepared in Example 3 were cut into halves respectively and then spliced ​​together to obtain a two-color electroluminescent matrix.

[0120] Example 5

[0121] This embodiment provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0122] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 18:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0123] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 70% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0124] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, uniformly dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane at 25°C and stirring at a speed of 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 4:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0125] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0126] (5) The electrode layer prepared in step (2) is transferred to the silicone oil paper as a soft substrate; after the elastic light-emitting layer 30 is transferred to the first electrode layer 20, the second electrode layer 40 is covered on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; VHB glue is respectively arranged as the first insulating layer 10 and the second insulating layer 50 on the opposite sides of the body to be packaged, and packaged into an electroluminescent matrix.

[0127] Example 6

[0128] This embodiment provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0129] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / calcium chloride solution with a molar ratio of 48:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0130] (2) The mixed solution obtained in step (1) was filtered through gauze to remove impurities. The selected gauze was 20 layers. After standing for a period of time, the solution was transferred to a silica gel membrane and spread evenly. The membrane was placed in a sealed environment at a temperature of 25°C and a relative humidity of 80% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0131] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, uniformly dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane at 25°C and stirring at a speed of 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 4:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0132] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0133] (5) The electrode layer prepared in step (2) is transferred to the silicone oil paper as a soft substrate; after the elastic light-emitting layer 30 is transferred to the first electrode layer 20, the second electrode layer 40 is covered on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; VHB glue is respectively arranged as the first insulating layer 10 and the second insulating layer 50 on the opposite sides of the body to be packaged, and packaged into an electroluminescent matrix.

[0134] Example 7

[0135] This embodiment provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0136] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 23:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0137] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 75% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0138] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, uniformly dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane at 25°C and stirring at a speed of 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 2:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0139] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0140] (5) The electrode layer prepared in step (2) is transferred to the silicone oil paper as a soft substrate; after the elastic light-emitting layer 30 is transferred to the first electrode layer 20, the second electrode layer 40 is covered on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; VHB glue is respectively arranged as the first insulating layer 10 and the second insulating layer 50 on the opposite sides of the body to be packaged, and packaged into an electroluminescent matrix.

[0141] Example 8

[0142] This embodiment provides a method for preparing an electroluminescent substrate, which comprises the following steps:

[0143] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 23:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0144] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 75% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0145] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, uniformly dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane at 25°C and stirring at a speed of 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 3:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0146] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0147] (5) The electrode layer prepared in step (2) is transferred to the silicone oil paper as a soft substrate; after the elastic light-emitting layer 30 is transferred to the first electrode layer 20, the second electrode layer 40 is covered on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; VHB glue is respectively arranged as the first insulating layer 10 and the second insulating layer 50 on the opposite sides of the body to be packaged, and packaged into an electroluminescent matrix.

[0148] Examples 9-12

[0149] The only difference between Examples 9-12 and Example 5 is that the mass ratios of SF and lithium chloride are 5:1, 4:1, 3:1 and 5:2, respectively.

[0150] Embodiment 13

[0151] (1) 10 g of silk fibroin was used as a raw material, dissolved in a formic acid / lithium chloride solution with a molar ratio of 46:1 for 10 minutes, and stirred at a speed of 150 r / min for 30 minutes to obtain a mixed solution; wherein the weight ratio of silk fibroin to formic acid was 1:10;

[0152] (2) filtering the mixed solution obtained in step (1) through gauze to remove impurities, wherein the selected gauze is 20 layers, and after standing for a period of time, transferring the solution to a silica gel membrane and spreading it evenly, and placing it in a closed environment at a temperature of 25° C. and a relative humidity of 75% for 96 hours to allow the solvent to completely evaporate, thereby forming an electrode layer composed of SF;

[0153] (3) using ZnS:Cu as the raw material of electroluminescent particles and strontium titanate as dielectric nanoparticles, dispersing the electroluminescent particles and dielectric nanoparticles in elastic polymer polydimethylsiloxane and stirring at 25°C and 100 r / min for 20 minutes to obtain a composite slurry; wherein the mass ratio of the electroluminescent particles to the elastic polymer is 4:5, and the mass ratio of the dielectric nanoparticles to the elastic polymer is 1:5;

[0154] (4) Spin coating the composite slurry obtained in step (3) on the surface of the PS substrate at a spin coating rate of 1000 r / min to form a film; placing the film in an environment of 60° C. for 1 hour to cure it to obtain an elastic light-emitting layer 30;

[0155] (5) The electrode layer prepared in step (2) is transferred to the silicone oil paper as a soft substrate; after the elastic light-emitting layer 30 is transferred to the first electrode layer 20, the second electrode layer 40 is covered on the elastic light-emitting layer 30 to achieve slow bonding to form a body to be packaged; VHB glue is respectively arranged as the first insulating layer 10 and the second insulating layer 50 on the opposite sides of the body to be packaged, and packaged into an electroluminescent matrix.

[0156] Application Examples

[0157] This embodiment provides a light-emitting device and a light-emitting method thereof, comprising: an electroluminescent substrate prepared in any one of the above embodiments 1-6, a sound sensor and a processor electrically connected to the electroluminescent substrate; wherein each electroluminescent substrate is electrically connected to the processor respectively and forms a preset pattern, Fig.11 Shown is a schematic diagram of a light emitting device attached to the back of a hand.

[0158] This embodiment provides a light emitting method of the light emitting device, comprising the following steps:

[0159] (1) Obtain external sounds;

[0160] (2) Determine the sound signal based on the external sound;

[0161] (3) Input the sound signal into a preset model to obtain a voltage signal;

[0162] (4) According to the voltage signal, the output voltage between the first electrode layer 20 and the second electrode layer 40 is controlled, so that the elastic light-emitting layer 30 is powered on and emits light to form a pattern signal matching the external sound.

[0163] For example, this embodiment can use a microphone as a sound sensor to collect different types of sound signals, and use a single-chip microcomputer as a processor to convert the collected sound signals into preset voltage signals. Specifically, the processor converts the sound signals into corresponding voltage signals of different levels according to preset classifications (for example, the 0-5V voltage signal is divided into 4 levels), and then uses a DC-AC inverter to increase the voltage to the corresponding power supply voltage and output it from the port of the corresponding single-chip microcomputer to the electrode body in the corresponding electrode layer, so that the electroluminescent substrate emits light in a pattern that matches the sound signal.

[0164] Since the frequency and size of the sound voltage signal are different, the frequency and brightness of the flicker are also different. By recording and classifying flickers of different frequencies and brightnesses, a sound classification model based on frequency and brightness information is constructed based on a machine learning algorithm. In addition, the sound sensor can also automatically capture the brightness changes of 150 frames (30 frames per second) corresponding to the calls of these animals in the dynamic display video of the light-emitting device according to a preset method, and pre-extract features through two one-dimensional convolutional layers, and then use three long short-term memory (LSTM) layers to obtain classification results, and establish the preset model, that is, the sound recognition model. When a new sound signal is input into the preset model, the model can automatically classify it and generate corresponding control signals to distinguish different types of sounds.

[0165] In another example, machine learning can be used to identify the type and frequency of the collected sound, and display it in real time on the interface of the computer terminal. At the same time, the microcontroller connected to the computer terminal converts the recognition result into a format, such as "utf-8", and outputs it to the electrode body in the corresponding electrode layer through the port of the corresponding microcontroller, so that the electroluminescent matrix emits light according to a pattern matching the sound signal.

[0166] In another example, the intelligent light-emitting device also includes a single-chip microcomputer electrically connected to the electroluminescent substrate, a display for recognizing sound and displaying the recognition result, and a converter for converting the recognition result into the "utf-8" format. When a sound signal is input, the display can display the recognition result in real time, and the converter converts the recognition result into a control signal in the "utf-8" format to drive the electroluminescent substrate to display the corresponding recognition result in real time. The device can provide real-time alarms and other services for hearing-impaired patients.

[0167] Take the animal sound recognition function as an example

[0168] 1) Collect a large number of cat, dog, tiger, elephant and bird calls, build a recognition model based on the convolutional neural network algorithm, and realize real-time recognition of animal call categories and their frequencies;

[0169] 2) Connect the model to the PC and use the tkinter library to build a human-computer interaction interface;

[0170] 3) The PC segment and the electroluminescent matrix are connected through a single-chip microcomputer. When an animal sound appears in the surrounding, the model receives and recognizes the sound, and transmits the electrical signal corresponding to the sound recognition result to the electroluminescent matrix. In addition, the human-computer interaction interface on the display and the surface of the electroluminescent matrix simultaneously display the pattern corresponding to the recognition result. For example, if a tiger's cry appears twice in the surrounding, the human-computer interaction interface displays "tiger-1" and the surface of the electroluminescent matrix displays "t-2", thereby realizing real-time sound warning. Fig.10 The luminous patterns corresponding to different sounds of the human-computer interaction interface are displayed.

[0171] Effect Example

[0172] (1) Mechanical properties test method: The mechanical test was performed using a tensile testing machine (Instron 5966, Instron, Norwood, USA) with a tensile rate of 50 mm / min. The two ends of the sample were fixed to the two end clamps of the testing machine, the frame height was adjusted so that the sample was at the zero load point, and the initial length, width, and thickness of the sample were measured.

[0173] Sample size: length: 10mm, width: 5mm, thickness: 0.5mm

[0174] (2) Luminescence performance test equipment: A spectrocolorimeter (PR655) was used to test the luminescence performance of the electroluminescent substrates prepared in Examples 1-6 and Comparative Example 1; the applied voltage during the luminescence test was 615V.

[0175] Table 1

[0176]

[0177]

[0178] Table 2

[0179] Stretched length <![CDATA[Luminous intensity (cd m -2 )]]> 0% 84 100% 85 200% 85 300% 85 400% 84 500% 77 600% 55 700% 26

[0180] Table 3

[0181] Cycle times <![CDATA[Luminous intensity (cd m -2 )]]> 0 times 84 1 time 84 100 times 84

[0182] Table 2 and Figure 6 The luminous intensity of the electroluminescent substrate A prepared in Example 2 at different stretching lengths can be seen from the data in Table 2 that the electroluminescent substrate prepared in the present invention can still maintain a luminous intensity equivalent to that in the initial state when the stretching length is 400%; and can still maintain luminescence when the stretching length is 700%.

[0183] Figure 7 It is demonstrated that both the electroluminescent substrates A and B of Examples 2 and 3 have good resilience.

[0184] Figure 8 Table 3 shows the luminous intensity of the electroluminescent substrate A prepared in Example 2 when cyclically stretched to 200%. It can be seen from the data in Table 3 that the electroluminescent substrate prepared in the present invention, when stretched to 200%, has a luminous intensity that remains at a level comparable to that of the initial state after 100 cycles.

[0185] Table 1 shows some process parameters and effect data of the embodiment and comparative example 1. As shown in Table 1, through the analysis of the performance parameters of the above embodiments 1 to 6, it can be known that the elongation at break of the electroluminescent substrates provided in the above embodiments 1 to 6 is all above 400%, and some can reach 600% or 800% or more, the fracture strength is not less than 0.2MPa, the Young's modulus is not less than 1.2MPa, and the toughness is not less than 1.6MJ m -3 , luminous intensity is 32cd m -2 -86cd m -2 Through the preparation method of the present invention, the content of the β-folded structure in the silk fibroin can be induced to be within a suitable range, thereby increasing the strength between the electrode layer and the elastic light-emitting layer and improving the overall elasticity of the electroluminescent matrix.

[0186] It can be seen from Examples 1 and 3 that increasing the mass ratio of SF to the conductive material in the electrode layer can increase its elongation at break and improve the luminous intensity. Fig.12 The relationship between the conductive properties and the mass ratio of SF to the conductive material in Example 3 and Examples 9-12 is recorded. Fig.13 The relationship between the luminous intensity, the mass ratio of SF and the conductive material, and the applied voltage in Examples 3 and 9-12 is described. Fig.12 and Fig.13 It can be seen that with the increase of the mass ratio of LiCl in the electrode layer, its conductivity gradually increases, resulting in an increase in luminous intensity, and when the mass ratio of SF:LiCi is greater than 3:1 or the mass ratio is 3:1-2:1, its luminous intensity can meet the use requirements and partially meet the luminous requirements of normal LEDs.

[0187] It can be seen from Examples 2, 7 and 8 that, with other factors remaining unchanged, in the elastic luminescent layer, as the ratio of the elastic polymer increases, its elasticity and tensile properties will be further improved, but at the same time it will also be accompanied by a significant decrease in the luminous intensity. Therefore, in order to ensure that the elastic luminescent layer has good elasticity and tensile properties while also having a good conductive effect as the electrode layer to ensure good luminous intensity, the mass ratio of the electroluminescent particles, the dielectric nanoparticles and the elastic polymer is set to (2-4):1:5, so that the electroluminescent matrix has good luminescent properties to achieve the role of replacing LED lamps, and thus has broad application prospects.

[0188] Figure 4 When the electroluminescent substrate prepared in Example 1 is attached to a finger, it can emit light to form different patterns. It can be seen that the electroluminescent substrate of the present invention has good flexibility and stretchability.

[0189] Figure 5 The schematic diagram of the electroluminescent substrate working normally under low and high temperature environment provided in Example 5. It can be seen that the electroluminescent substrate of the present invention can emit light normally at a temperature of 7.5°C or 90°C, indicating that the electroluminescent substrate of the present invention is suitable for extreme weather conditions of high or low temperature.

[0190] Fig. 9 This is the luminescence of the electroluminescent substrates A and B in Example 4 during the process of stretching to 300% after being spliced. It can be seen that the spliced ​​substrate can maintain luminescence during the stretching process. It can be seen that the electroluminescent substrate provided by the present invention has good self-healing properties. After it is cut into two parts as luminous skin, by re-contacting along the cross section of the cut electrodes and applying an AC electric field, the two electrodes can be repaired by self-healing and emit light normally, and their brightness is not significantly different from that before the electroluminescent substrate is cut. Therefore, it can still maintain a good luminous state in the case of self-healing. Therefore, through this performance, luminous skins of different luminous colors can be spliced, and a stable two-color luminous state can be achieved.

[0191] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0192] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An electroluminescent substrate, characterized in that: It includes a first insulating layer, a first electrode layer, an elastic light-emitting layer, a second electrode layer and a second insulating layer in sequence; Wherein, the first electrode layer and the second electrode layer both include conductive material and silk fibroin; Wherein, the elastic light-emitting layer comprises electroluminescent particles and elastic polymer.

2. The electroluminescent substrate according to claim 1, characterized in that The conductive material includes a metal salt; the metal salt is preferably a lithium salt and / or a calcium salt; More preferably, the lithium salt is lithium chloride and / or lithium bromide; More preferably, the calcium salt is calcium chloride; More preferably, the silk fibroin and the Li + The mass ratio is (12-18):1, such as 12:1, 17:1 or 18:1; More preferably, the silk fibroin and the Ca in the calcium salt 2+ The mass ratio is (5-8):1, for example 6:1; And / or, the silk fibroin at least includes silk fibroin in a β-folded conformation; And / or, the electroluminescent particles include ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are preferably ZnS:Cu particles and / or ZnS:Al particles; And / or, the elastic luminescent layer comprises dielectric nanoparticles; the dielectric nanoparticles preferably comprise strontium titanate and / or barium titanate; And / or, the elastic polymer includes one or more of polydimethylsiloxane, polyurethane and silicone rubber, and the polyurethane is preferably water-based polyurethane; And / or, the first insulating layer and the second insulating layer are both formed of acrylic adhesive, such as transparent acrylic foam adhesive.

3. The electroluminescent substrate according to claim 1, characterized in that The first insulating layer and the second insulating layer are connected at their edges and encapsulate the first electrode layer, the elastic light-emitting layer and the second electrode layer; And / or, the first electrode layer and the second electrode layer each include a plurality of electrode layer units cut into different shapes and / or the same shape, and the electrode layer units are arranged continuously or discontinuously; and the electrode layer units of the same shape in the first electrode layer and the second electrode layer are arranged in a one-to-one correspondence; And / or, the first electrode layer and the second electrode layer are provided with electrical connection parts electrically connected to an external power source, and the electrical connection parts are preferably conductive metal wires; And / or, the thickness of the elastic light-emitting layer is 0.05 mm-0.5 mm, for example 0.1 mm; and / or, the thickness of the first electrode layer and the second electrode layer are independently selected from 0.05 mm to 0.5 mm, for example 0.15 mm; And / or, the thicknesses of the first electrode layer and the second electrode layer are the same or different.

4. A method for preparing an electroluminescent substrate, characterized in that: It includes the following steps: S1. preparing the mixed solution into an electrode layer; the mixed solution comprising silk fibroin, a conductive substance and a solvent; The composite slurry is prepared into an elastic luminescent layer; the composite slurry comprises electroluminescent particles and an elastic polymer; The electrode layer and the elastic light-emitting layer are prepared in any order; S2. The electrode layers are respectively arranged at the opposite ends of the elastic light-emitting layer, which are respectively recorded as the first electrode layer and the second electrode layer, and the first electrode layer and the second electrode layer are encapsulated by the first insulating layer and the second insulating layer to obtain the electroluminescent matrix.

5. The method for preparing an electroluminescent substrate according to claim 4, characterized in that: The conductive material includes a metal salt; the metal salt is preferably a lithium salt and / or a calcium salt; More preferably, the lithium salt is lithium chloride and / or lithium bromide; More preferably, the calcium salt is calcium chloride; More preferably, the silk fibroin and the Li + The mass ratio is (12-18):1, such as 12:1, 17:1 or 18:1; More preferably, the silk fibroin and the Ca in the calcium salt 2+ The mass ratio is (5-8):1, for example 6:1; And / or, the silk fibroin at least includes silk fibroin in a β-folded conformation; and / or, the solvent is one or more of water, ethanol and formic acid; And / or, the mass ratio of the silk fibroin to the solvent is (0.1-20):100, for example 10:100; And / or, the mass ratio of the conductive material to the solvent is (0.1-10):100, preferably (1-6):100, for example 1:27, 1:23, 1:18 or 1:48; And / or, the electroluminescent particles include ZnS particles and / or Mn particles doped with metal elements, and the ZnS particles doped with metal elements are preferably ZnS:Cu particles and / or ZnS:Al particles; And / or, the composite slurry further comprises dielectric nanoparticles; the dielectric nanoparticles preferably comprise strontium titanate and / or barium titanate; the mass ratio of the dielectric nanoparticles to the elastic polymer is preferably (1-50):100, more preferably (10-40):100, for example 1:5; more preferably, the mass ratio of the electroluminescent particles, the dielectric nanoparticles and the elastic polymer is (2-4):1:5, for example 2:1:5 or 4:1:5; And / or, the elastic polymer includes one or more of polydimethylsiloxane, polyurethane and silicone rubber, and the polyurethane is preferably water-based polyurethane; and / or, the mass ratio of the electroluminescent particles to the elastic polymer is (1-20):10, preferably (2-15):10, for example 4:5 or 2:5; And / or, both the first insulating layer and the second insulating layer are formed of acrylic adhesive, such as transparent acrylic foam.

6. The method for preparing an electroluminescent substrate according to claim 4, characterized in that: In step S1, the preparation method of the mixed solution comprises the following steps: first dispersing the conductive material in the solvent, and then dispersing the silk fibroin therein; wherein the dispersion is preferably completed under stirring, and the stirring rate is 100r / min-1000r / min, such as 150r / min; the dispersion time of the silk fibroin is preferably 5min-60min, such as 40min; And / or, in step S1, the temperature for preparing the electrode layer is 25-60°C, for example 25°C; And / or, in step S1, the time for preparing the electrode layer is 48h-240h, for example 96h; And / or, in step S1, the relative humidity of the environment for preparing the electrode layer is 60%-90%, preferably 65%-85%, for example 65%, 70%, 75% or 80%; And / or, in step S1, the preparation of the electrode layer is carried out in a closed environment; And / or, in step S1, the electrode layer is prepared by placing the mixed solution on a substrate and drying it to obtain the electrode layer; And / or, in step S1, the preparation method of the composite slurry comprises: dispersing the electroluminescent particles and the dielectric nanoparticles in an elastic polymer to form the composite slurry; the dispersion time is preferably 60 seconds; the dispersion temperature is preferably 25°C; And / or, in step S1, the preparation method of the elastic luminous layer is to coat the composite slurry on a substrate to form the elastic luminous layer; wherein the substrate is preferably PS and / or PET; the coating method is preferably spin coating, spray coating or scraping coating; more preferably, the spin coating rate is 200r / min-5000r / min, for example, 1000r / min; the coating is preferably cured; more preferably, the curing temperature is 20°C-60°C, for example, 60°C; more preferably, the curing time is 5min-120min, for example, 60min; And / or, in step S1, the elastic luminescent layer is further subjected to a hydrophilic treatment; the hydrophilic treatment method is preferably at least one of an ultraviolet method, an ozone method and a plasma cleaning method; the hydrophilic treatment time is preferably 10s-60s; And / or, in step S1, the first electrode layer and the second electrode layer each include a plurality of electrode layer units cut into different shapes and / or the same shape, and the electrode layer units are arranged continuously or discontinuously; and the electrode layer units of the same shape in the first electrode layer and the second electrode layer are arranged in a one-to-one correspondence; And / or, in step S2, an electrical connection portion electrically connected to an external power source is provided in the electrode layer, and during the packaging process, the electrical connection portion is exposed to the outside; the electrical connection portion is preferably a conductive metal wire.

7. The method for preparing an electroluminescent substrate according to claim 6, characterized in that: In step S1, in the mixed solution, the conductive substance is lithium bromide, the solvent is water, and the concentration of lithium bromide is 4-8 mol / L; Or, in step S1, in the mixed solution, the conductive substance is calcium chloride, the solvent is ethanol and water, and the molar ratio of calcium chloride, ethanol and water is 1:2:(6-10); Or, in step S1, in the mixed solution, the conductive substance is lithium chloride, the solvent is formic acid, and the molar ratio of lithium chloride to formic acid is 1:(20-50); Or, in step S1, in the mixed solution, the conductive substance is calcium chloride, the solvent is formic acid, and the molar ratio of calcium chloride to formic acid is 1:(40-100).

8. An electroluminescent substrate, characterized in that It is prepared according to the preparation method described in any one of claims 4 to 7.

9. A light emitting device, characterized in that: The invention comprises the electroluminescent substrate, sensor and processor as described in any one of claims 1 to 4 and 8.

10. A method for controlling the light emission of the light emitting device according to claim 9, characterized in that: It includes the following steps: Get external signals; Inputting the signal into a preset model to obtain a voltage signal; According to the voltage signal, the output voltage between the first electrode layer and the second electrode layer is controlled, so that the elastic light-emitting layer is powered on and emits light, so as to form a pattern signal matching the external signal.